(untitled) (Itinerarios Educativos, 2020)
This article presents an experience dealing with a network developed by trainers of educators in the field of Natural Sciences working in six Higher Education Institutes in the province of Santa Fe, Argentina, during the period of preventive and mandatory social isolation due to the Covid-19 pandemic. Suspension of teaching activities in traditional physical spaces and the subsequent irruption of the distance education model as an alternative to give continuity to training processes at Higher Education was an event that urged to be faced. The initial confusion gave way to a collective, plural, and cooperative initiative, framed in an interinstitutional research project through collaborative networking that prevented us from being trapped by immobility. The work –fully developed by means of digital communication technologies– not only allowed us to build knowledge about Natural Science teaching practices developed in primary schools along the first weeks of the quarantine, but it also generated a democratic and participatory environment in virtual communities. This exchange of diverse knowledge, materials, and experiences enriched us at both professional and human level. The present work addresses our effort to systematize the group experience.